The Impact of RNA Interference on Atherosclerotic Plaque Progression: A Meta-Analysis of Preclinical Studies - R. Ifan Arief Fahrurozi; Akmal M Hanif; Taufik Rizkian Asir; Wahyudi (HM Publisher, 2025)
Background: Atherosclerosis, a chronic inflammatory disease characterized by the buildup of plaque within arteries, remains a leading cause of cardiovascular morbidity and mortality. RNA interference (RNAi) has emerged as a promising therapeutic strategy for atherosclerosis by targeting genes involved in plaque formation and progression. This meta-analysis aimed to evaluate the efficacy of RNAi in preclinical models of atherosclerosis. Methods: A systematic search of PubMed, Embase, and Web of Science databases was conducted from January 2013 to December 2023 to identify preclinical studies investigating the impact of RNAi on atherosclerotic plaque progression. Studies utilizing various RNAi modalities (siRNA, miRNA mimics/inhibitors, shRNA) targeting different genes involved in atherosclerosis were included. The primary outcome was plaque size reduction. Secondary outcomes included changes in plaque composition, lipid profiles, and inflammatory markers. A random-effects model was used to pool data and calculate standardized mean differences (SMD) with 95% confidence intervals (CI). Heterogeneity was assessed using the I² statistic. Results: Seven preclinical studies met the inclusion criteria, encompassing a total of 210 animals. RNAi interventions significantly reduced atherosclerotic plaque size compared to controls (SMD -1.51; 95% CI -2.36 to -0.66; p<0.00001; I²=12%). Analysis of secondary outcomes revealed favorable effects of RNAi on plaque composition, with a significant decrease in lipid content and an increase in collagen content. Furthermore, RNAi significantly improved lipid profiles by reducing total cholesterol and LDL-cholesterol levels. A significant reduction in inflammatory markers, such as TNF-α and IL-6, was also observed. Conclusion: This meta-analysis provides compelling evidence supporting the therapeutic potential of RNAi in attenuating atherosclerotic plaque progression in preclinical models. RNAi effectively reduced plaque size, improved plaque stability, and modulated lipid metabolism and inflammation.